Peningkatan Keterampilan Menulis Karangan Melalui Model Pembelajaran Concept Sentence pada Siswa Kelas V SD Muhammadiyah 11 Mangkuyudan Tahun 2015/2016 - Wihida, Refianti (2016)
This research aims to determiner whether to the model of Concept Sentence can improved essay writing skills in class V students of SD Muhammadiyah 11 Mangkuyudan 2015/2016 years. The research subject is fifth grade teacher and fifth grade students of SD Muhammadiyah 11 Mangkuyudan number of 38 students. This research is a class act. The meeting was conducted over two cycles or four meetings. The collecting of data through observation, interviews, documentation and testing. As for triangulation of data sources using triangulation and triangulation techniques. Data analysis techniques used is the reduction, data presentation and verification. The results showed an increase in essay writing skills are at the stage of pre-cycle of 39.47% (15 students who have reached KKM of 38 students). At this stage of the cycle I in the first meetings to increase to 52.63% (20 students who have reached KKM of 38 students). At this stage of the cycle II in the second meeting increased to 60.52% (23 students who have reached KKM of 38 students). The stage of the second cycle in the first meeting increased to 71,05% (27 students who have reached KKM of 38 students). In the second cycle phase at the second meeting increased to 81,57% (31 students who have reached KKM of 38 students). The conclusion of this research is the Concept Sentence strategy can improve essay writing skills in class V students of SD Muhammadiyah 11 Mangkuyudan